POPULATION PARAMETERS OF RED SNAPPER (Lutjanus malabaricus) IN ARAFURA SEA FMA 718 - Ayuningtyas, Okky Arista; Kasim, Kamaluddin; Imran, Zulhamzah; Kodiran, Taryono (Politeknik Kelautan dan Perikanan Sorong, 2023)
The utilization of red snapper (Lutjanus malabaricus) in Arafura waters is already at its optimum point and is classified as over-exploited. Information on population parameters is needed so that management can be sustainable. This study aims to determine several aspects of population parameters (Lc, Lm, L, t0, K, Z, M, F, E). The data collection method uses red snapper sampling including sex, length, and total weight in the 2021-2022 fishing period at PPP Mayangan, Probolinggo. The total number of red snapper samples was 3,077 with the smallest length being 19 cm and the largest being 89 cm. The results showed a relationship between length and weight W = 4,106.10-2 L1,730 with a value of b = 1,730, meaning that b < 3 indicates a negative allometric growth pattern. Average length caught (Lc = 50 cmTL) < Average length at maturity (Lm = 52 cmTL). Based on the Von Bertalanffy model formula, the growth parameter values are obtained, namely asymptotic length (L∞) = 96 cm, growth coefficient (K) = 0.72 per year, and age at zero length (t0) = -0.789. The growth equation is Lt = 96[1-e-0,72 (t-(-0,789))]. The value of natural mortality (=M) is 1.04 per year and the value of mortality due to fishing (=F) is 1.39 per year so the total mortality (=Z) is 2.43 per year. The exploitation value/utilization rate (=E) is 0.57. This shows that the utilization level has experienced more capture and reached the optimum level.